Genetics of destemming in pepper: A step towards mechanical harvesting - Hill, Theresa; Cassibba, Vincenzo; Joukhadar, Israel; Tonnessen, Bradley; Havlik, Charles; Ortega, Franchesca; Sripolcharoen, Sirisupa; Visser, Bernard Jurriaan; Stoffel, Kevin; Thammapichai, Paradee; Garcia-Llanos, Armando; Chen, Shiyu; et al. (Frontiers in Genetics, 2023)
The majority of peppers in the US for fresh market and processing are handpicked, and harvesting can account for 20- 50% of production costs. Innovation in mechanical harvesting would increase availability; lower the costs of local, healthy vegetable products; and perhaps improve food safety and expand markets. Most processed peppers require removal of pedicels (stem and calyx) from the fruit, but lack of an efficient mechanical process for this operation has hindered adoption of mechanical harvest. In this paper, we present characterization and advancements in breeding green chile peppers for mechanical harvesting. Specifically, we describe inheritance and expression of an easy-destemming trait derived from the landrace UCD-14 that facilitates machine harvest of green chiles. A torque gauge was used for measuring bending forces similar to those of a harvester and applied to two biparental populations segregating for destemming force and rate. Genotyping by sequencing was used to generate genetic maps for quantitative trait locus (QTL) analyses which revealed a major destemming QTL on chromosome 10 that was found across populations and environments. Eight additional population and/or environment-specific QTL were also identified. Chromosome 10 QTL markers were used to help introgress the destemming trait into jalapeño-type peppers. Low destemming force lines combined with improvements in transplant production enabled mechanical harvest of destemmed fruit at a 39% higher rate compared with a commercial jalapeño hybrid. Staining for the presence of lignin at the pedicel/fruit boundary indicated the presence of an abscission zone and homologs of genes known to affect organ abscission were found under several QTL, suggesting that the easy-destemming trait may be due to the presence and activation of a pedicel/fruit abscission zone. Presented here are tools to measure the easy-destemming trait, its physiological basis, possible molecular pathways, and expression of the trait in various genetic backgrounds. Mechanical harvest of destemmed mature green chile fruits was achieved by combining easy-destemming with transplant management.